1+1=5 : and Other Unlikely Additions - David LaRochelle (New York, United States Sterling Juvenile, 2010)
This title is suitable for children aged 5 years and up. How much is 1+1? Think the answer is 2? Not always, as this playful approach to addition proves! David LaRochelle takes children on a joyful mathematical journey that will engage their minds and teach them to think about numbers in a creative, outside-the-box way. Brenda Sexton's wild and wacky illustrations add layers of witty fun to LaRochelle's clever game.
Keywords: Math stories -- Math stories